The Readiness of Science Teachers to Implement Differentiated Learning and Integrated STEM in Ecology Subject of the “Merdeka” Curriculum in Junior High School - Nikmatin Mabsutsah; Slamet Hariyadi; Jekti Prihatin (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Each student in the class has different abilities, readiness, and interests in learning. As the provider of materials and as a facilitator, the teacher must be able to adapt to curriculum changes, including enhancing students' creative thinking skills through differentiated and integrated STEM learning in the subject of ecology for grade 7 in junior high school. This research aims to analyze the readiness of science teachers to implement differentiated and integrated STEM learning in the “merdeka” curriculum of junior high school. The analytical method used is quantitative descriptive, employing a semi-open questionnaire consisting of 16 questions. The research subjects are 15 science teachers of grade 7 in junior high schools in Besuki. The questionnaire analysis results show that 66.7% of the teachers have implemented differentiated learning under the principles of the merdeka curriculum. However, they face several constraints, such as time, learning resources, facilities, infrastructure, and lack of training and experience teaching differentiated learning. 33.3% of science teachers who have integrated STEM into the ecology subject also encounter constraints such as time, availability of electricity, availability of materials, internet connection, and lack of training. 0% of science teachers have not yet used differentiated STEM-integrated ecology modules. Thus, 100% of the teachers agree with the development of differentiated STEM-integrated ecology modules, as teachers need learning media that can assist in implementing differentiated STEM-integrated learning.